The Effect of Using an Exercise-Nutrition Program on Some Physiological Variables on Diabetes Patients - Sherin Hussien; Dina Farouk Atef Morad; Naglaa Mohamed Abdelhamid Ibrahim; Mohammed Nader Shalaby (Indian Journal of Forensic Medicine & Toxicology, 2021)
The tremendous and astonishing technological progress in the modern era in all different fields has ledto a lack of human mobility and thus a lack of physical and physiological competence, which made himvulnerable to many diseases called hypokinetic diseases such as cardiovascular disease, obesity, lower backpain, diabetes, and high blood pressure. The Study Problem: Diabetes is one of the most common andwidespread diseases today, and failure to control this disease will lead to many complications, includingcardiovascular disease, high-fat content, in addition to limb muscle atrophy, high blood pressure andperipheral nerve inflammation, which sometimes leads to leg amputation. The cause of death and this is thesource of the problem. The Study Objectives: Knowing the blood sugar level of non-athletic patients aged40-55 years before the program. Designing an athletic program for diabetics aged 40-55 years who are nonathletes for the research group. To know the effect of the program on blood sugar, HDL cholesterol, and PCVblood viscosity for the research group. Identify the effect of the program on the nerve signals received fromthe upper and lower extremities of the research group. The study community the human field: people withdiabetes who are 40-55 years old who are not athletes. from 1/3/2020 to 1/7/2020. Hospitals and specializedcenters for treating this disease and the Physiotherapy Center for Sports Medicine in Egypt. Results: thevalues of the blood sugar test indicate the significance of the differences between the pre-and post-tests andin favor of the post-test, considering that the drop in blood sugar level is a positive case. blood HDL ratiotest indicates the significance of the differences between the pre-and post-tests and in favor of the post-test,considering that the drop in blood sugar level is a positive case. blood HDL ratio test considering the highlevel of HDL cholesterol is a positive case. Conclusions: 1-The diet and exercise program has a positiveeffect on low blood sugar levels. 2-The sports and nutritional program have a positive effect on the levelof high-density lipoprotein (HDL) cholesterol in the blood. 3-The sports and nutritional program have apositive effect on blood viscosity (PCV). 4-The sports and nutritional program have a positive effect on thenerve signals coming from the upper and lower extremities.